High levels of lipoprotein(a) are associated with the severity of coronary disease in patients with acute myocardial infarction. Data from the RICO survey. (14th October 2021) - Farnier, M; Chague, F; Maza, M; Bichat, F; Beer, J C; Masson, D; Cottin, Y; Zeller, M; ,
Abstract: Background: High level of lipoprotein(a), Lp(a), is a well-recognized independent risk factor for atherosclerotic cardiovascular disease (ASCVD) including acute myocardial infarction (MI). However, limited data are available on the relationship between coronary artery disease (CAD) burden and Lp(a) levels in patients with acute MI. Methods: CAD burden was addressed in 1213 consecutive patients hospitalized for an acute MI in 2019–2020 who underwent coronary angiography from the RICO survey. Patients were compared according to Lp(a) levels (Lp(a) <50 mg/dL (normal), ≥50 mg/dL and ≤100 mg/dL (high) and >100 mg/dL (very high)). Results: The prevalence of high and very high Lp(a) was elevated (13% and 6%, respectively). Median (IQR) age (normal: 68 (58–79)y; high: 70 (61–80)y; very high: 69 (60–78)y, p=0.502) and rate of diabetes (p=0.448) were similar across the 3 groups. When compared with normal Lp(a), patients with very high Lp(a) had more frequently hypertension, were more often under chronic statin therapy and their corrected LDL-cholesterol was lower. There was a gradual increase in prior ASCVD rates across the 3 Lp(a) groups (p=0.001). When compared with patients with high or normal Lp(a), patients with very high Lp(a) levels had elevated SYNTAX score at coronary angiography, (17 (6–25) vs 12 (6–19) and 10 (5–18), p=0.006, respectively), and had more frequently multivessel disease (74% vs 64% and 56%, p=0.003). By multivariate analysis, very high Lp(a) (OR(95% CI): 1.879 (1.065–3.312)) remained associated with high CAD burden, beyond confounding including age, diabetes and dyslipidemia. Conclusion: Among real world patients hospitalized for an acute MI, high Lp(a) levels are common (≈20%) and independently associated with a severe CAD burden, beyond traditional risk factors, identifying a subset of patients with features of high ASCVD risk. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): CHU Dijon Bourgogne ARS Bourgogne Franche Comté